Evaluation of different strains of Agaricus bisporus for higher yield and other quality character under Kashmir conditions - Munshi, N A; Kauser, Shaheen; Rehman, Shabir U; Teli, Mushtaq Ahmad; Peerzada, S H (Mushroom Research, 2012)
In Kashmir valley button mushroom cultivation is still done through rural oriented labourintensive technology under natural condition in some rooms of the residential houses, employing long method of composting. In the present study a number of commercial strains obtained from different sources were evaluated for their yield ability over a period of three years (2007-2009). The prime aim of the work was to identify a suitable high yielding strain of button mushroom and make it available to the growers.